Роль освіти у формуванні міжкультурної компетентності - Шарова, Тетяна Михайлівна; Sharova, Tetiana (Запоріжжя : ТДАТУ, 2025)
UA: У статті розглядається роль освіти у формуванні міжкультурної компетентності як важливого чинника ефективної взаємодії в умовах глобалізації. Аналізуються основні методи навчання, що сприяють розвитку міжкультурної компетентності, зокрема метод занурення, міжкультурне моделювання, проєктний підхід, кейс-стаді та рефлексивне навчання. Окреслено основні труднощі, що виникають у процесі міжкультурної освіти, та запропоновано шляхи їх подолання. Наголошено на важливості інтеграції міжкультурної складової в освітні програми на всіх рівнях, а також на ролі цифрових технологій та міжнародних програм у цьому процесі. /// EN: The article examines the role of education in the formation of intercultural competence as a key factor in effective interaction in the context of globalization. The main teaching methods that contribute to the development of intercultural competence are analyzed, including the immersion method, intercultural simulation, project-based learning, case study, and reflective learning. The main challenges arising in the process of intercultural education are outlined, and ways to overcome them are proposed. Emphasis is placed on the importance of integrating the intercultural component into educational programs at all levels, as well as on the role of digital technologies and international programs in this process.
The role of education in the formation of intercultural competence
Keywords: міжкультурна компетентність; освіта; глобалізація; методи навчання; міжкультурна взаємодія; міжкультурні бар’єри; стереотипи; академічна мобільність; цифрові технології; intercultural competence; education; globalization; teaching methods; intercultural interaction; intercultural barriers; stereotypes; academic mobility; digital technologies